Breast Self-Examination Education and Training (SADARI) as an Early Detection Effort for Breast Cancer in Women of Childbearing Age - Puspita Ningrum, Nyna; Ayu Cahya Rosyida, Desta; Latifah, Anik; Hidayatunnikmah, Nina (Yayasan Education and Social Center, 2025)
Breast cancer is one of the most common types of cancer in women and is the leading cause of cancer death in women in various parts of the world. Early detection is a crucial step in increasing the success of treatment and reducing mortality rates. One easy-to-do early detection method is Breast Self-Examination (BSE), which is an examination carried out independently, regularly, and systematically by every woman to find abnormalities or lumps in the breasts from an early stage. This Community Service (PkM) activity aims to increase the understanding of mothers and young women about the importance of early detection of breast cancer through the BSE method. The activity was carried out in Pengaingan Hamlet, Bangkalan District, involving participants from among students of Madrasah Diniyah Al Munawaroh and local mothers. The methods used included interactive counseling, BSE demonstrations, and question and answer sessions. The results of the activity showed an increase in participants' knowledge about breast cancer and their ability to perform BSE independently. It is hoped that this activity can encourage healthy living behavior and awareness of the importance of early detection as a preventive measure against breast cancer.